The complete sequence of mitochondrial genome of polled yak (Bos grunniens). (3rd May 2016) - Chu, Min; Wu, Xiaoyun; Liang, Chunnian; Pei, Jie; Ding, Xuezhi; Guo, Xian; Bao, Pengjia; Yan, Ping
Abstract: Generally speaking, the hornless trait is also known as polled. Although the POLL locus could be assigned to a 1.36-Mb interval in the centromeric region of BTA1 (Georges et al., 1993; Drögemüller et al., 2005)), and (Liu et al., 2014) reported a 147-kb segment that included three protein-coding genes was the most likely location of the POLL mutation in domestic yaks, the underlying genetic basis for the polled trait is still unknown. In this work, the complete mitochondrial genome sequence of polled yak was determined for the first time. The total length of the mitogenome is 16, 324 bp long, with the base composition of 33.72% A, 27.25% T, 25.83% C, and 13.20% G. It contained 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and 1 non-coding region (D-loop region). The gene order of polled yak mitogenome is identical to that observed in most other vertebrates. The complete mitogenome sequence information of polled yak will provide useful data for further studies on protection of genetic resources and phylogenetic relationships within Bos grunniens .